Clinical Characteristics, Laboratory, Maternal and Fetal Outcomes in Pregnancy with Covid-19 at RSUP dr. M. Djamil Padang - Roza Sriyanti; Heri Farnas; Dovy Djanas (Andalas Obstetrics And Gynecology Journal, 2024)
Introduction : The data obtained from various studies about covid-19 conducted in severalhospitals in the world are currently considered not sufficient to provide a clinical picture thatoccurs in pregnancies with Covid-19 infection. The aims to provide an overview of the clinical,laboratory, maternal and fetal outcomes in pregnancy with Covid-19 infection at dr. M. DjamilPadang.Methods: This study used a descriptive design with data collection starting from March 01,2020 - March 31, 2021 based on medical record data. Carried out in a single center at RSUPdr. M. Djamil Padang in pregnant patients with confirmed Covid-19 by PCR examination.Results: Total 136 pregnant patients confirmed Covid-19 by PCR examination. Most of thesymptoms were asymptomatic (47.1%) and without any comorbidities (76.5%). There were 3patients who experienced critical symptoms (2.2%). Maternal mortality was found at 2.3% andfetal death 4.7%. The values of d-dimer and NLR were found increasing significantly,2025.35±1392.18 for d-dimer and 6.39±4.43 for NLR. Pregnancy terminations done for 77.9%patients with cesarean section is the most method (83%). There were 4 cases (3.8%) of babiesinfected with Covid-19 from mothers who had pregnancy terminations.Conclusions: Most cases had asymptomatic clinical symptoms (47.1%). There are 2.3%cases of maternal death and 4.7% cases of fetal death. Most of the pregnancy terminationswere performed by cesarean section (88%). On laboratory examination, there was a significantincrease in maternal d-dimer (2,025.35±1.392.18) and NLR (6.39±4.43) in pregnancies withCovid-19.